On the Need to Teach Vocabulary Directly in the Primary and Secondary Levels of the Argentine Education System - Zapico, Martín Gonzalo (2017)
In the Argentine educational system today we live a crisis situation, which becomes evident when high school graduates must face a college major: They do not have the basic skills of reading and writing, which results in a high dropout rate in the first year. This state of affairs, among other things, can be attributed to an approach that chose to ignore the direct teaching of vocabulary learning, postulating that it can be indirectly learned. On this basis we propose that the direct teaching of vocabulary is necessary to promote not only a better academic performance but a better quality of life in general. To argue this position, we will request the opinion of teachers, experts in the field, theoretical studies and practical experience, highlighting the urgency of a return to these practices to promote vocabulary development in a world that tends increasingly to the economy of language